The Treatment of Phenol in Batik Wastewater by TiO2 -Copper Oxide (CuO And Cu2O) Photocatalyst - Afifah, Dini Nur; Riyani, Kapti; Setyaningtiyas, Tien; Hasanah, Yeti Rusmiati; Mufarij, Adam (Jurnal Kartika Kimia, 2022)
Phenol is an organic material in batik waste that must be processed before disposal because it is carcinogenic and can reduce dissolved oxygen levels. The method used to treat phenol is Advanced Oxidation Process (AOPs). The AOPs method is a waste treatment technology with free radicals to degrade pollutants into CO2 and H2O. Oxidizing agents are hydroxyl radicals (•OH) produced by certain materials, one of which is TiO2. Although proven capable of degrading organic pollutants, the use of TiO2 still encounters a reasonably significant band gap energy constraint for TiO2 (3.2 eV). The modifications carried out in this study were the addition of copper (Cu) dopants to reduce the TiO2 band gap and electron trapping to prevent electron and hole recombination. The synthesis of TiO2-Cu oxide was carried out by deposition method using TiO2 and CuCl2.5H2O as Cu precursors. The results showed that the addition of Cu to TiO2 reduced the band gap energy up to 2.25 eV. The data showed that phenol treatment using TiO2:Cu (98:2) for 6 hours at pH 2, under the influence of a tungsten lamp, could reduce phenol up to 98.03%. The photodegradation process with TiO2:Cu ratio and the same pH can occur more quickly with a UV lamp for 2 hours. The amount of phenol that can be degraded under these conditions is 98.23%. Keywords: Phenol, TiO2, TiO2 doped Cu Oxide